Hinduistiske helligsteder i religionsfænomenologisk og forskningsteoretisk belysning - Sand, Erik Reenberg (Religionsvidenskabeligt Tidsskrift, 1984)
The subject of the present article is the tírthas or sacred places in Hinduism. The first part deals with the manifold concept of tírtha, by giving a general phenomenological analysis of the concept in relation to what is called hierophanies and theophanies, and by giving a geographical survey of the more well-known tírthas. The second part shows how the tírtha as a phenomenon reflects the problem of different levels in Hinduism. First the theories of M.N. Srinivas, concerning “spread” and “sanscritization”, and of R. Redfield and M. Singer, concerning the dichotomy between “the Great Tradition” and “the Little Tradition”, as well as some of the criticism of these theories are being discussed. Secondly, it is shown, by help of the results of the cultural geographer S.M. Bhardwaj, how the tírthas might be particularly helpful in the attempt to systematically uncover these levels. Finally, some more general considerations are set forth about the significance of these methodological problems for the more traditional, textually based History of Religion.